Estimation of Serum Magnesium level among Patients with Bronchial Asthma in Erbil -Iraq - Saidoka, Kamaran Mahmud; Zangana, Salam Naser; Lak, Rebaz Tahir (Diyala Journal of Medicine, 2019)
Background:Bronchial asthma is a common chronic respiratory disease worldwide. Although magnesium (Mg) deficiency has been shown to play a role in exacerbation of asthma, the exact prevalence of hypomagnesaemia in asthma is not clear. Objective: To estimate the serum Mg levels in bronchial asthma patients and compare them with healthy population and to evaluate the prevalence of hypomagnesaemia among them. Patients and Methods: A cross-sectional study was carried out in the respiratory unit of Rizgary Teaching Hospital involving 80 adult patients with chronic asthma (group I) and 80 healthy adult controls (group II). Serum magnesium level was measured in all the participants. Results: Hypomagnesaemia was detected in 20% of the asthmatic patients when compared to controls (0%) (p=0.001). No significant association was detected between magnesium status and type of asthma (p= 0.59). There was a statistically significant stage-wise decline in serum levels of Mg with increase in severity of asthma (p=0.02). Patients with severe asthma had the highest prevalence of hypomagnesaemia (45.5%) in comparison to mild and moderate cases (p=0.001). No significant associations were detected between the level of magnesium and the number of medications that the patients used, corticosteroids use, and theophylline therapy (p=0.06, 0.17, and 0.08, respectively). Hypomagnesaemia was significantly correlated with the duration of asthma (p=0.04). Conclusion: Hypomagnesaemia is more prevalent in chronic asthmatics than non-asthmatics. Hypomagnesaemia was significantly correlated with severity and duration of asthma.